(untitled) (Veterinary Science, 2025)
This report presents the case of a young adult male canine, not neutered, exhibiting clinical signs consistent with a perineal hernia (tenesmus, constipation, deformity of the perineum, etc.). The patient underwent abdominal ultrasonography, which revealed large cystic structures associated with the prostate gland, causing displacement of abdominal organs. Prior to surgical intervention, a tomographic evaluation was performed to delineate the affected structures with greater precision. During the surgical procedure, the cystic lesions were addressed, with omentalization of the residual tissue. Additionally, colopexy and cystopexy were performed without the need for pelvic diaphragm repair. A negative culture was obtained, and histopathology was consistent with a cystic structure. The recovery was uneventful up to the date of this report, exceeding 12 months. This report aims to highlight the importance of preoperative imaging modalities, their complementary role, and the relevance of surgical techniques such as prostatic omentalization, combined with colopexy and cystopexy, for a comprehensive and effective management of such cases